DETERMINATION OF CONTAMINATION LEVELS OF HEAVY METALS LEAD (Pb) AND CADMIUM (Cd) IN FOOD SAMPLES BY CARBON ATOMIC ABSORPTION SPECTROPHOTOMETRY (GRAPHITE FURNACE ATOMIZER AAS/ GF-AAS) - Oktavia, Dwina Putri; Panggabean, Aman Sentosa; Pasaribu, Subur P.; Widodo, Nanang Tri (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Research on the determination of lead (Pb) and cadmium (Cd) heavy metal contamination levels using the GFA-AAS method has been carried out in food samples. The aim of this study was to determine the levels of lead (Pb) and cadmium (Cd) metal contamination so that they do not exceed the threshold limit set according to the Food and Drug Supervisory Agency Regulation No. 9 of 2022. The research was carried out by destroying the sample using HNO3(p) and H2O2(p) into microwave. Additions were made of matrix modifiers (mixture of Mg(NO3)2. 6H2O in 0,5% HNO3 and 1% NH4H2PO4 in 0,5% HNO3 (1:1)). Determination of heavy metal content in food was determined by the Carbon Furnace Atomic Absorption Spectrophotometry (GFA-AAS) method with a wavelength of 283.3 nm for lead (Pb) and 228.8 nm for cadmium (Cd). The results of measuring the levels of heavy metal lead (Pb) contamination in food samples were 0,016 mg/kg and 0,015 mg/kg for the heavy metal cadmium (Cd). Based on the Regulation of the Food and Drug Supervisory Agency No 9 of 2022 concerning Requirements for Heavy Metal Contamination in Processed Foods, the maximum limit for metal contamination of lead (Pb) and cadmium (Cd) in processed food is 0,30 mg/kg, where the results obtained do not exceed threshold, so that the sample is fit for consumption. Keywords: Lead, Cadmium, Carbon Furnace Atomic Absorption Spectrophotometry, Food.